Closing the Gender Profit Gap? - Catia Batista; Sandra Sequeira; Pedro C. Vicente (Institute of Labor Economics (IZA), 2021)
We examine the impact of providing access to mobile savings accounts and improving financial management skills on the performance of female-led microenterprises in Mozambique. We find evidence that both interventions can improve business performance but the effects are highly heterogeneous. Combining both types of support is associated with a large increase in both short and long-term firm profits and in financial security for the microentrepreneur. This allowed female-headed microenterprises, particularly those with a higher baseline level of profits, to close the gender profit gap in performance and skills relative to their male counterparts. The main drivers of improved business performance are improved financial management practices (bookkeeping), an increase in accessible savings, and reduced transfers to friends and relatives. For female entrepreneurs with intermediate levels of profits at baseline, even just providing access to mobile money accounts can increase long-term profits and for the most disadvantaged microentrepreneurs it can at least in-crease levels of financial security. Uncovering this heterogeneity in impact within different types of female-led microenterprises can help improve the targeting of these interventions in the future.
Keywords: O15; O16; G53; J16; 330; microenterprise development; management; gender; mobile money; financial literacy; economic development